The Role of Person-Environment Fit in Mediating The Effects of Company Culture toward Employees’ Turnover Intention in PT. Berca Hardayaperkasa - Tinjung Desy Nursanti; Masruroh Masruroh; Andela Putri Maharani (Bina Nusantara University, 2015)
The purpose of this study was to investigate the mediating effect of person-environment fit on the relationship between organizational culture and staff turnover intention. Data were obtained from permanent employees who were working in unit business at PT.Berca Hardayaperkasa (n = 75). This research method is explanatory survey. This type of research is associative. The analysis used in this study is a path analysis. The results indicate that the organizational culture has a significant influence to the staff turnover intention and person-environment fit has a significant mediating influence on the relationship between organizational culture with staff turnover intention.